2017
DOI: 10.1016/j.econedurev.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impacts of an unconditional cash transfer program on child schooling: Experimental evidence from Malawi

Abstract: This study analyzes the impact of a positive income shock on child schooling outcomes using experimental data from an unconditional cash transfer program in Malawi. Since households receive the cash and parents are responsible for making spending decisions, we also examine the intervening pathways between cash transfers and child schooling. Data comes from a cluster-randomized study of Malawi’s Social Cash Transfer Program (SCTP). After a baseline survey, households in village clusters were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…In consumption terms, SCT transfers comprise about 20 percent of pre‐program per capita consumption for the average household (Kilburn et al. )…”
Section: Motivations and Drivers Of Private Intergenerational Transfementioning
confidence: 99%
See 2 more Smart Citations
“…In consumption terms, SCT transfers comprise about 20 percent of pre‐program per capita consumption for the average household (Kilburn et al. )…”
Section: Motivations and Drivers Of Private Intergenerational Transfementioning
confidence: 99%
“…Despite advantages incurred by beneficiaries of this program (Ellis and Maliro ; Ellis and Manda ; Kilburn et al. ; Miller et al. ; Nanivazo ), on a societal level, the implications of the SCT program on transfer patterns and within‐family income pooling and/or insurance provision are limited, as coverage rates of the SCT and related programs remain low (ILO ).…”
Section: Motivations and Drivers Of Private Intergenerational Transfementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both programs were found to increase child school attendance, yet non‐negligible increases were also found in child work participation (both in household entrepreneurial activities and household chores) as children played a role in helping with household productive investment (de Hoop, Groppo, and Handa ; Kilburn et al. ). In addition, analysis from Malawi indicates that programs increased household resilience and ability to cope with shocks, and mental health of youth aged 13 to 19 at baseline (UNC ; Angeles et al.…”
mentioning
confidence: 99%
“…Previous analysis examining the impacts of the Social Cash Transfer Program (SCTP) and Multiple Category Targeted Grant (MCTG) on primary outcomes has concluded that at the household level, both programs increased consumption, food security, material welfare and assets, and strengthened livelihoods and productive investment, while decreasing monetary poverty (UNC 2016;Fisher et al 2017;Brugh et al 2018;). In addition, both programs were found to increase child school attendance, yet non-negligible increases were also found in child work participation (both in household entrepreneurial activities and household chores) as children played a role in helping with household productive investment (de Hoop, Groppo, and Handa 2017;Kilburn et al 2017). In addition, analysis from Malawi indicates that programs increased household resilience and ability to cope with shocks, and mental health of youth aged 13 to 19 at baseline (UNC 2016;Angeles et al 2017).…”
mentioning
confidence: 99%